Optical approach based omnidirectional thermal visualization - Wong, W.K.; Loo, C.K.; Lim, W.S. (2010)
In this paper, a new optical approach based on omnidirectional thermal visualization system is proposed. It will provides observer or image processing tool a 360 degree viewing of surrounding area using a single thermal camera. By applying the proposed omnidirectional thermal visualization system even in poor lighting condition, surrounding area is under proper surveillance and the surrounding heating machineries/items can be monitored indeed. Infrared(IR) reflected hyperbolic mirrors have been designed and custom made for the purpose of reflecting omnidirectional scenes in infrared range for the surrounding area to be captured on a thermal camera, thus producing omnidirectional thermal visualization images. Five cost effective and market-common IR reflected materials used to fabricate the designed hyperbolic mirror are studied, i.e. stainless steel, mild steel, aluminum, brass, and chromium. Among these materials, chromium gives the best IR reflectivity, withÎµr = 0.985. Specifically, we introduce log-polar mapping for unwarping the captured omnidirectional thermal image into a panoramic view, hence providing observers or image processing tools a complete wide angle of view. Three mapping techniques are proposed in this paper namely the point sample, mean sample and interpolation mapping techniques. Point sample mapping technique provides the greatest interest due to its lower complexity and moderate output image quality.